Estimasi Cooling Load Ruang Penyimpanan Bunga Mawar Potong Pasca Panen di Kab. Bandung Jawa Barat Indonesia - Paweka, Bagiawati Rahayu; Berman, Ega Taqwali (Universitas Negeri Makassar, 2017)
People's perception of cut flowers more positive, the use not only limited to mere decoration, but also for religious activities, sympathy, and so forth. Then the need for cut flowers always increases. But the constraints of this product are easily damaged, whether it occurs when picking or storage; shelf life and short cut flower life; and the influence of the storage environment of interest on damage that increases post-harvest losses. The purpose of this research is to get the value of cooling loads of post-harvest flower storage space of 28,000 stems at 10 0C and 90% RH. Based on the literature study from various sources in the design of cooling space, it is produced that the heat load to be handled by cooling machine unit is 163.484,79 Btu/hr or 13,62 TR.Keywords: estimation, storage room, cut flowers.